Sharps including needlestick injuries in Australian nurses practising in New South Wales. (19th October 2011) - Guest, Maya; Kable, Ashley
Abstract : Objectives: To determine nurse-reported period prevalence of Sharps Injuries including Needlesticks (SIN) in the past 12 months, factors associated with SIN in NSW and compare data across workplace categories and geographic regions. Methods: A cross-sectional survey was conducted of a representative sample of nurses from the NSW Nurses' Association membership in 2007. The sample (n=7423) was selected representing nurses from 5 workplace categories. Results: The reported period prevalence of 1 or more SIN involving a used sharp by respondents in the sample group (n=1301) was 6.5%. This study suggests that SIN rates in the respondent group were higher in the clinical areas of emergency room, operating theatres, medical and surgical wards, mental health and aged care. No differences were found between workplace or nursing award categories, however a significant increase was observed in remote areas. For participants with SIN, a high proportion reported the injury and less than half believed they were at risk for contracting a bloodborne disease. Overall, participants reported that policies were followed in the event of an SIN incident; however, some respondents reported recapping after drawing up medications and after administering medications or obtaining blood samples. Conclusions: This study suggests that SIN prevalence remains a significant OH&S issue for the profession; some clinical areas may have a higher risk. Reporting of SIN incidents is high but less than desired. Policies for following up SIN incidents have high reported compliance, however respondents reported a less than desirable compliance with the no recapping policy (NSW Health:PD2007_036).